Metacognitive Beliefs and Their Relation with Symptoms in Obsessive-Compulsive Disorder - Tümkaya, Selim (Noro Psikiyatr Ars, 2018)
INTRODUCTION: Metacognitive constructs have shown promise in explaining the symptoms of Obsessive-Compulsive Disorder (OCD). Few studies have examined the role of metacognitions in symptom dimensions of OCD, despite mounting clinical, neuropsychological and imaging evidence for the distinctiveness of these dimensions. METHODS: Metacognitions were assessed using the Metacognitions Questionnaire (MCQ-30) in 51 participants with DSM IV OCD and 46 healthy controls. The Maudsley Obsessional Compulsive Inventory (MOCI) was used to quantify symptom dimensions, along with the Hamilton Anxiety Rating Scale (HAM-A) for anxiety, and Hamilton Depression Rating Scale (HAM-D) for depression. RESULTS: Individuals with OCD differed from healthy controls on beliefs of uncontrollability and danger when depression and anxiety were controlled for. Correlations between metacognitive beliefs and obsessive-compulsive symptom dimensions were largely similar across the OCD and healthy control groups. Hierarchical regression showed that need to control thoughts contributed to checking, cleaning and rumination symptoms; cognitive self-consciousness to symptoms of slowness; uncontrollability and danger to doubt symptoms; positive beliefs to checking symptoms. CONCLUSIONS: Specific associations between metacognitive variables and the different symptom dimensions of OCD are evident, however, severity of anxiety and depression also contribute to these associations.